2014
DOI: 10.18869/acadpub.johe.3.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders in the general population referring to a medical educational center in Rasht, Iran

Abstract: Background: Mental disorders in patients with chronic medical disorders are associated with, performance degradation, poor quality of life, lack of cooperation with treatment and inappropriate use of medical services, and increased costs. The objective of this study was to determine the prevalence of mental disorders in the general population referring to an educational medical hospital in Rasht, Iran, in 2013. Materials and Methods: In this cross-sectional study, 1725 patients who referred to a medical educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…In line with other studies ( 10 , 44 , 45 ), the current study’s findings showed a positive association among depression and anxiety symptoms and a history of job loss, mental illness, feeling hopeless about the future, and having other medical conditions. The strongest association in this area was with feeling hopeless about the future; those who felt hopeless about the future were 5.38 and 3.33 times more likely to experience depression and anxiety symptoms, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with other studies ( 10 , 44 , 45 ), the current study’s findings showed a positive association among depression and anxiety symptoms and a history of job loss, mental illness, feeling hopeless about the future, and having other medical conditions. The strongest association in this area was with feeling hopeless about the future; those who felt hopeless about the future were 5.38 and 3.33 times more likely to experience depression and anxiety symptoms, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…According to the findings of previous studies ( 44 , 45 ), there was an inverse association between depression symptoms and high economic status in the present study. The high prevalence of mental disorders in those with low economic status may be due to a number of factors, including not having enough income to meet even the most basic needs, the need for entertainment, the monotony of life, and a lack of hope for the future ( 40 , 44 , 45 ).…”
Section: Discussionsupporting
confidence: 88%